Salmonella typhi contains identical intervening sequences in all seven rrl genes. - Mattatall, N R (1996)
Salmonella typhi Ty2 rrl genes contain intervening sequences (IVSs) in helix-25 but not in helix-45 on the basis of observed 23S rRNA fragmentation caused by IVS excision. We have confirmed this and shown all seven IVSs to be identical by isolating genomic DNA fragments containing each of the seven rrl genes from S. typhi Ty2 by use of pulsed-field gel electrophoresis; each rrl gene was amplified by PCR in the helix-25 and helix-45 regions and cycle sequenced. Thirty independent wild-type S. typhi strains, tested by genomic PCR and DraI restriction, also have seven rrl genes with helix-25 IVSs and no helix-45 IVSs. We propose that IVS homogeneity in S. typhi occurs because gene conversion drives IVS sequence maintenance and because adaptation to human hosts results in limited clonal diversity.